2015
DOI: 10.1177/194008291500800112
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Butterflies, Bats and Beetles as Bioindicators Based on Four Key Criteria and DNA Barcodes

Abstract: Informed conservation decision-making requires meaningful biodiversity assessment, yet performing an inventory of all species present at a site is an impossibility. A small group of species is frequently used as a proxy for "total" biodiversity, and various attributes required by bioindicator groups have been suggested. We synthesized these suggestions as four key criteria: i) tractable taxonomy, ii) easily surveyed, iii) broadly distributed higher taxa but specialized species, and iv) diversity patterns refle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 46 publications
1
30
0
1
Order By: Relevance
“…However, the species richness of fruit-feeding nymphalids has been reported to increase with age of secondary forest fragments on Sulawesi, Indonesia, as the temperature and humidity are regulated by the increased canopy density (Veddeler et al 2005). Although several studies have suggested the pattern of species distribution along rural-urban gradients are affected by the surrounding landscape matrix (Öckinger et al 2009;Lizée et al 2012;Syaripuddin et al 2015), we found no clear association between the park species richness and the distance of the park from the urban core (the central business district)-similar to findings in Guangzhou (Li et al 2009) and Kuala Lumpur (Sing et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, the species richness of fruit-feeding nymphalids has been reported to increase with age of secondary forest fragments on Sulawesi, Indonesia, as the temperature and humidity are regulated by the increased canopy density (Veddeler et al 2005). Although several studies have suggested the pattern of species distribution along rural-urban gradients are affected by the surrounding landscape matrix (Öckinger et al 2009;Lizée et al 2012;Syaripuddin et al 2015), we found no clear association between the park species richness and the distance of the park from the urban core (the central business district)-similar to findings in Guangzhou (Li et al 2009) and Kuala Lumpur (Sing et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The close association between grasses and Satyrine species in this study could signal a higher potential for use as indicators of forest condition. Such an attribute can be beneficially exploited to help direct limited conservation resources in economically disadvantaged areas and for prioritising conservation efforts such as identifying priority sites for formal protection or steering restoration efforts [27]. Another reason that could account for these variations in species compositions between the two study areas is the extent and impact of human activities or environmental stressors such as agricultural expansion and intensification, infrastructure development, settlement expansion and pollution which according to Bonebrake et al [4] and Gardner et al…”
Section: Discussionmentioning
confidence: 99%
“…A biodiversity inventory is simply a list of biological entities at a site (Stork & Davies ), but it is essential data for those tasked with managing and conserving biodiversity (e.g., providing justification for gazetting protected areas) (Syaripuddin et al. ). Biodiversity inventories take time and expertise.…”
Section: Dna Barcoding and Biodiversity Inventorymentioning
confidence: 99%